Strategi Bauran Pemasaran Dalam Mengokohkan Citra Merek - Faisal Reza (ArtComm, 2020)
Demand for food and drink needs outside the home is increasing in relation to the activities of each human being. The business that can be done by culinary business is to provide good service quality so that customers feel satisfied and decide to come back to the restaurant. Imah Babaturan Coffee Shop is one of the restaurants in the city of Bandung which has a location that is not too strategic. The Imah Babesian Coffee Shop also has a relatively high price range of products and the community around the Imah Babesian Coffee Shop are mostly from the lower middle class. This research uses descriptive qualitative research methods. The method of data collection is done by interviews and observations which are expected to provide in-depth information so that the writer can obtain accurate information about the marketing mix strategy undertaken by Warung Kopi Imah Babaturan in strengthening brand image. The conclusion that can be drawn from this research is that if a business has its own uniqueness without having to position its products, an effort will be attached to its own image in the minds of consumers. Like the Warung Kopi Imah Babaturan, the historical uniqueness of the location and the product are more accepted by consumers